Analisis Deskriptif Model Pembelajaran Al Islam Terhadap Peningkatan Hasil Belajar Siswa Kelas VII SMP Muhammadiyah 02 Kalisat - Mohammad Risal Akbar; Sofyan Rofi; Dhian Wahana Putra (Ameena Journal, 2026)
The implementation of Al-Islam learning models has an important role in improving students’ cognitive learning outcomes, especially in understanding Islamic materials. Learning processes that are less varied often cause students to have difficulties in understanding, remembering, and explaining the material presented. Therefore, learning models that are able to create an active, effective, and enjoyable learning atmosphere are needed for seventh-grade students at SMP Muhammadiyah 02 Kalisat. This study aims to describe the Al-Islam learning models in improving the cognitive learning outcomes of seventh-grade students at SMP Muhammadiyah 02 Kalisat. This study employed a qualitative approach with a descriptive research type. The research subjects consisted of Al-Islam teachers and seventh-grade students. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing to obtain a clear description of the implementation of Al-Islam learning models. The implementation of Al-Islam learning models was carried out through interactive lectures, cooperative learning, contextual learning, direct learning, analogy learning, and the use of humor in the learning process. These learning models were able to improve students’ cognitive abilities in understanding, remembering, analyzing, and explaining Al-Islam materials. Students became more active and found it easier to understand the material because the teacher used communicative and interactive approaches adjusted to learning needs. Thus, the Al-Islam learning models at SMP Muhammadiyah 02 Kalisat contributed positively to improving the cognitive learning outcomes of seventh-grade students.